2021
DOI: 10.1186/s12862-020-01732-2
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal gene transfer and recombination analysis of SARS-CoV-2 genes helps discover its close relatives and shed light on its origin

Abstract: Background The SARS-CoV-2 pandemic is one of  the greatest  global medical and social challenges that have emerged in recent history. Human coronavirus strains discovered during previous SARS outbreaks have been hypothesized to pass from bats to humans using intermediate hosts, e.g. civets for SARS-CoV and camels for MERS-CoV. The discovery of an intermediate host of SARS-CoV-2 and the identification of specific mechanism of its emergence in humans are topics of primary evolutionary importanc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 76 publications
(114 reference statements)
3
53
0
Order By: Relevance
“…According to these authors, not only pangolins, but also other mammals -such as small carnivores-would be candidates. With respect specifically to pangolins, Makarenkov et al (2021) provided arguments supporting the hypothesis of the SARS-CoV-2 origin, according to which, the SARS-CoV-2 genome was a chimera of the RaTG13 and pangolin coronaviruses. Moreover, the results of their horizontal gene transfer and recombination analysis suggested that SARS-CoV-2 could not only be a chimera virus resulting from recombination of the bat RaTG13 and pangolin coronaviruses, but also a close relative of the bat CoV ZC45 and ZXC21 strains.…”
Section: Zoonotic Origin Of Sars-cov-2mentioning
confidence: 85%
“…According to these authors, not only pangolins, but also other mammals -such as small carnivores-would be candidates. With respect specifically to pangolins, Makarenkov et al (2021) provided arguments supporting the hypothesis of the SARS-CoV-2 origin, according to which, the SARS-CoV-2 genome was a chimera of the RaTG13 and pangolin coronaviruses. Moreover, the results of their horizontal gene transfer and recombination analysis suggested that SARS-CoV-2 could not only be a chimera virus resulting from recombination of the bat RaTG13 and pangolin coronaviruses, but also a close relative of the bat CoV ZC45 and ZXC21 strains.…”
Section: Zoonotic Origin Of Sars-cov-2mentioning
confidence: 85%
“…There have been two recent investigations of HGT and recombination in coronaviruses using phylogenetic reconciliation approaches [14,29] (performed independently in parallel to the current work). Fu et al [14] used DTL reconciliation to infer inter-host HGT events using approximately 400 coronavirus genomes, including alpha, beta, delta, and gamma coronaviruses from a variety of host species.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting reconciliations were used to identify the host species that were most likely to engage in cross-host-species recombination of coronaviruses. Makarenkov et al [29] used phylogenetic techniques to investigate patterns of HGT and recombination in 11 gene families from Sarbecoviruses. In particular, the authors use the HGT detection program T-Rex [6], based on bipartition dissimilarity between a strain tree and gene trees, to identify partial-and full-gene HGTs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pangolin-CoV is identical to SARS-CoV-2 in all five critical residues for receptor binding of the RBD but has only 92% whole-genome nucleotide identity [ 117 ]. Analysis of horizontal gene transfer and recombination lends support for intragenic recombination of the spike genes between RaTG13 and Pangolin-CoV, which could have given rise to the chimeric SARS-CoV-2 [ 118 ]. However, neither RaTG13 nor Pangolin-CoV contain the polybasic furin cleavage site at the S1/S2 junction, which is present within the spike protein of SARS-CoV-2 and greatly contributes to the virus’s tropism and pathogenicity [ 119 ].…”
Section: Origins Of Sars-cov-2 and Hiv-1mentioning
confidence: 99%